Dietary Fiber Intake Alters Gut Microbiota Composition but Does Not Improve Gut Wall Barrier Function in Women with Future Hypertensive Disorders of Pregnancy - Tomsett, Kate I. (Nutrients, 2020)
Pregnancy alters the inflammatory state, metabolic hormones, and gut microbiota composition. It is unclear if the lower abundance of dietary fiber-fermenting, short-chain fatty acid-producing bacteria observed in hypertension also occurs in hypertensive disorders of pregnancy (HDP). This study investigated the relationship between dietary fiber intake and the gut microbiota profile at 28 weeks gestation in women who developed HDP in late pregnancy (n = 22) or remained normotensive (n = 152) from the Study of PRobiotics IN Gestational diabetes (SPRING). Dietary fiber intake was classified as above or below the median of 18.2 g/day. Gut microbiota composition was examined using 16S rRNA gene amplicon sequencing. The gut permeability marker zonulin was measured in a subset of 46 samples. In women with future HPD, higher dietary fiber intake was specifically associated with increased abundance of Veillonella, lower abundance of Adlercreutzia, Anaerotruncus and Uncl. Mogibacteriaceae and higher zonulin levels than normotensive women. Fiber intake and zonulin levels were negatively correlated in women with normotensive pregnancies but not in pregnancies with future HDP. In women with normotensive pregnancies, dietary fiber intake may improve gut barrier function. In contrast, in women who develop HDP, gut wall barrier function is impaired and not related to dietary fiber intake.